Political Narrative About The Fake Diploma Controversy on an Online News Portal - Farida Yufarlina Rosita; Ani Rakhmawati; Kundharu Saddhono (Aksara, 2025)
This study aims to investigate how political realities are discursively constructed in media texts and to uncover the underlying power relations and ideological frameworks embedded in the narratives of CNN Indonesia’s news portal. This research employs a qualitative descriptive approach using observation and note-taking techniques applied to six news articles concerning Jokowi’s alleged fake diploma. Data analysis adopts Norman Fairclough’s three-dimensional CDA framework: (a) text analysis, (b) discourse practice, and (c) sociocultural practice. The findings suggest that CNN Indonesia, while maintaining a formal and ostensibly objective tone, employs strategic lexical choices, grammatical structures, and rhetorical strategies to legitimize state authority and shift public focus away from the substance of the allegations toward the legal proceedings against the accusers. The news employs a legalistic and institutional tone that appears neutral but implicitly fosters public trust in state institutions and skepticism toward civil criticism. This study highlights that media discourse is never entirely neutral and plays a critical role in reproducing power structures through carefully constructed narratives. AbstrakPenelitian ini bertujuan untuk menyelidiki realitas politik yang dibangun secara diskursif dalam teks-teks media dan mengungkap hubungan kuasa serta kerangka ideologis yang tertanam dalam narasi-narasi portal berita CNN Indonesia. Penelitian ini merupakan penelitian deskriptif kualitatif dengan teknik observasi dan pencatatan pada enam artikel berita tentang ijazah palsu Jokowi yang diterbitkan pada Mei 2025. Analisis data penelitian menerapkan tiga kerangka kerja Analisis Wacana Kritis menurut Norman Fairclough: (a) analisis teks, (b) praktik wacana, dan (c) praktik sosiobudaya. Hasil menunjukkan bahwa, meskipun CNN Indonesia mempertahankan nada formal dan tampak objektif, terdapat penggunaan strategi leksikal, struktur gramatikal, dan retorika untuk melegitimasi pemerintah negara dan mengalihkan perhatian publik dari tuduhan yang dibuat ke proses hukum terhadap mereka yang dituduh. Berita tersebut menggunakan nada hukum dan institusional yang tampak netral, tetapi secara tidak langsung meningkatkan kepercayaan masyarakat terhadap institusi negara. Penelitian ini menekankan bahwa diskursus media tidak pernah sepenuhnya netral, dan bahwa itu sangat penting untuk menggambarkan struktur kekuasaan melalui cerita yang direncanakan dengan baik.